EVALUATION OF MEDICINAL PLANTS (QUERCUS INFECTORIA AND ASTRAGALUS ERIOCEPHALUS) AS FEED ADDITIVES IN AWASSI EWE’S RATION 1. DIGESTIBILITY, MILK YIELD AND COMPOSITION - & et al., Merkhan (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2019)
To evaluate the impact of two medicinal plants Quercus infectoria and Astragalus eriocephalus on digestibility, milk yield, its compositions and economic efficiency, twenty eight lactating Awassi ewes at their mid-lactation were selected based on their pre-treatment milk yield, were divided into four groups and fed ration containing 1% Gall oak, 2% Astragalus, 0.5% Gall oak with 1% Astragalus, and Control. Twelve ewe lambs were used to study the effect of rations on the digestibility. Herbal active compounds were obtained by GC-MS analysis. Results revealed that fifty-six and twenty-four compounds identified in Astragalus eriocephalus and Quercus infectoria samples, with the major compound being P-Cymene and Carvacrol, respectively. Ewes fed Astragalus diets showed significantly (P<0.05) higher digestibility dry and organic matter. Daily and 0.4 FCM milk yield in treated groups were significantly (P<0.05) higher than control. Milk composition were significantly (P<0.05) affected by diet treatment. Economic and relative efficiency were better in treated groups than the control. It can be concluded that supplementing herbal plants to the lactating ewes’ diet improve their digestibility, milk yield and economic efficiency.